Immunomodulatory effects of mesenchymal stem cells for the treatment of cardiac allograft rejection. Issue 7 (April 2021) - Wu, Zhichao; Liang, Jialiang; Huang, Wei; Jiang, Lin; Paul, Christian; Gao, Xiang; Alam, Perwez; Kanisicak, Onur; Xu, Meifeng; Wang, Yigang
Heart transplantation continues to be the gold standard clinical intervention to treat patients with end-stage heart failure. However, there are major complications associated with this surgical procedure that reduce the survival prognosis of heart transplant patients, including allograft rejection, malignancies, infections, and other complications that arise from the use of broad-spectrum immunosuppression drugs. Recent studies have demonstrated the use of mesenchymal stem cells (MSCs) against allotransplantation rejection in both in vitro and in vivo settings due to their immunomodulatory properties. Therefore, utilization of MSCs provides new and exciting strategies to improve heart transplantation and potentially reduce the use of broad-spectrum immunosuppression drugs while alleviating allograft rejection. In this review, we will discuss the current research on the mechanisms of cardiac allograft rejection, the physiological and immunological characteristics of MSCs, the effects of MSCs on the immune system, and immunomodulation of heart transplantation by MSCs.